Preparation method of high-wear-resistance and high-strength large-specification aluminum oxide ceramic ball
By employing multi-stage refining and homogenization processes, segmented spray granulation, servo press preforming, automated bagging and vacuum processing, ultra-high pressure cold isostatic pressing, and high-temperature sintering technologies, the problem of preparing large-size alumina ceramic balls has been solved, and high-wear-resistant and high-strength ceramic balls have been prepared.
Patent Information
- Application Number
- CN202511396605.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-09-28
AI Technical Summary
Existing technologies have shortcomings in material selection, process optimization, and performance improvement in preparing large-sized alumina ceramic balls with high wear resistance and high strength. In particular, there is room for improvement in the sintering uniformity, internal stress distribution, and wear resistance of large-sized ceramic balls.
The main raw materials are processed using a multi-stage refining and homogenization device, combined with segmented spray granulation, servo press preforming, automated bagging and vacuum treatment, ultra-high pressure cold isostatic pressing and high temperature sintering technology to ensure uniform grain growth and densification.
It significantly improves the molding quality and overall performance of large-size alumina ceramic balls, reduces surface defects, ensures the densification and wear resistance of the green body, and realizes the preparation of high wear-resistant and high-strength ceramic balls.
Smart Images

Figure CN120864872A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic material preparation technology, specifically a method for preparing large-sized alumina ceramic balls with high wear resistance and high strength. Background Technology
[0002] Currently, the preparation methods for high-performance ceramic balls are mainly based on research findings on fused zirconia and silicon nitride materials. Compared to alumina, these methods exhibit certain limitations in specific application scenarios. Patent document CN103232238B discloses a method for preparing high-strength fused zirconia ceramic balls. This method involves ultrafine grinding of monoclinic fused zirconia powder with a ZrO2+HfO2 content of over 99.6%, combined with spray granulation, cold isostatic pressing, sintering, and polishing processes, to prepare ceramic balls with a density exceeding 6.00 g / cm³ and a hardness exceeding 1250 (HV). However, this technical solution does not address the optimization of the preparation process for large-size ceramic balls, and the wear resistance of fused zirconia is somewhat inferior to that of alumina, limiting its applicability in high-wear-resistance applications.
[0003] Patent document CN113461426B discloses a dense, high-hardness, and high-strength silicon nitride ceramic ball and its preparation method. The method involves mixing Si3N4 powder, MgO powder, and Yb2O3 powder, followed by ball milling, cold isostatic pressing, pre-firing, and spark plasma sintering. This produces ceramic balls with uniform composition distribution, few internal defects, and high density, hardness, and strength. However, this technology uses silicon nitride as the main raw material, resulting in high production costs. Furthermore, its toughness is inferior to alumina, making it difficult to completely replace alumina in large-size ceramic ball applications. Additionally, this method does not address how to solve the cracking and deformation problems caused by the increased size of large-size ceramic balls during sintering.
[0004] The aforementioned problems indicate that existing ceramic ball preparation technologies still have room for improvement in terms of material selection, large-scale process optimization, and overall performance enhancement. In particular, for large-sized alumina ceramic balls requiring high wear resistance and high strength, current technologies still need improvement in areas such as sintering uniformity, internal stress distribution, and wear resistance optimization. Therefore, this invention provides a method for preparing large-sized alumina ceramic balls with high wear resistance and high strength. Summary of the Invention
[0005] A method for preparing large-sized alumina ceramic balls with high wear resistance and high strength includes introducing a multi-stage refining and homogenization device in the main raw material processing stage to generate a slurry suitable for subsequent processing; using segmented spray granulation technology to convert the slurry into powder with specific physical properties; completing the initial preforming through a servo press to form a preformed green body; performing automated bagging, vacuuming, and heat sealing treatment on the preformed green body to reduce surface defects; using ultra-high pressure cold isostatic pressing technology to achieve secondary densification and increase the relative density of the green body; performing programmed temperature sintering in a high-temperature environment to ensure uniform grain growth and densification; and conducting comprehensive performance testing on the finished product to verify its physical, mechanical, and microstructural characteristics.
[0006] The main raw material processing stage includes the following steps:
[0007] S11. Accurate Weighing and Feeding of Raw Materials: Alumina micro-powder with an α-phase purity of 90% to 99.99% is selected as the main raw material, with its D50 median particle size controlled within the range of 0.35 micrometers to 0.45 micrometers, and its specific surface area controlled between 12.5 m² / g and 14.5 m² / g; polyvinyl alcohol (PVA) with a molecular weight of 1750±50 and a degree of hydrolysis of 98.5±0.5% is selected as the binder, with its addition amount being 1.8% to 2.2% of the dry weight of the main raw material; ammonium polyacrylate is selected as the dispersant, with its addition amount being 0.45% to 0.55% of the dry weight of the main raw material; Polyethylene glycol (PEG-400) is used as a plasticizer, with an addition amount of 0.9% to 1.1% of the dry weight of the main raw material; oleic acid is selected as a lubricant, with an addition amount of 0.5% to 0.6% of the dry weight of the main raw material; the above-mentioned components, weighed to an accuracy of one ten-thousandth, are added together with deionized water into a ball mill jar, wherein the resistivity of the deionized water is not less than 18 megohm-cm, the ball mill jar is an intermittent ball mill lined with high alumina (92 or 95 alumina), the ball milling media is (92 or 95 alumina), its diameter is 3 mm to 10 mm, and the ball-to-material mass ratio is controlled at 3.5:1 to 4.5:1;
[0008] S12. Intermittent ball milling: Start the intermittent ball mill and set the rotation speed to 20 to 30 revolutions per minute. Wet mill continuously for 28 to 32 hours in an environment with a temperature control of 22±2 degrees Celsius. During this period, the outer wall temperature of the tank is maintained at no more than 40 degrees Celsius through a circulating water jacket cooling system. After the ball milling is completed, the slurry is tested with an online laser particle size analyzer to ensure that the D90 particle size of the slurry is no greater than 0.95 micrometers.
[0009] S13. Iron removal and aging of slurry: The ball-milled slurry is passed through a high-gradient electromagnetic iron remover with a magnetic flux density of 1.2 Tesla to remove magnetic impurities that may have been mixed in during the grinding process. The iron-removed slurry is then transferred to a stainless steel aging tank with a slow stirring device and sealed for aging for 48 to 60 hours at a negative pressure of 0.01 MPa and a temperature of 25 ± 3 degrees Celsius to promote the uniform adsorption and hydrolysis of organic additives.
[0010] Spray granulation technology includes the following steps:
[0011] S21. Slurry conveying and atomization: The aged slurry is conveyed to the atomizer of the centrifugal spray granulation tower via a peristaltic pump. The flow rate of the peristaltic pump is precisely controlled between 25.0 liters / hour and 30.0 liters / hour. The atomizer is a high-speed centrifugal type with a disc diameter of 120 mm and a rotation speed set between 18,000 rpm and 22,000 rpm.
[0012] S22. Drying and Collection: The inlet hot air temperature of the spray drying tower is set to 175°C to 185°C, and the outlet temperature is set to 90°C to 100°C. A slight negative pressure is maintained inside the tower. The dried powder is collected in two stages through the discharge valve at the bottom of the main tower and a cyclone separator, ensuring a collection efficiency of greater than 99.5%.
[0013] S23. Powder performance characterization and screening: The collected granulated powder is subjected to performance testing. The moisture content is required to be controlled between 0.40% and 0.60%, the loose density is required to be between 0.90 g / cm³ and 1.05 g / cm³, the tapped density is required to be between 1.15 g / cm³ and 1.30 g / cm³, and the flowability is measured by a Hall effect flow meter, requiring the flow rate to be less than or equal to 25.0 seconds / 50 g. The powder is screened using 200 mesh and 300 mesh standard sieves. Only the powder that passes through the 200 mesh sieve and is retained in the 300 mesh sieve is used for subsequent pressing and molding.
[0014] Servo press preforming includes the following steps:
[0015] S31. Precise feeding by servo press: A servo press with a closed-loop control system is adopted, with a pressure control accuracy of ±0.1%FS and a position control accuracy of ±0.005 mm; through an integrated weighing feeding system linked with the press control system, the screened qualified powder is precisely filled into the mold cavity, and the mass error of each feeding is controlled within ±0.05%; the mold is made of cemented carbide (WC-Co), and its inner surface is treated with diamond-like carbon (DLC) coating with a coating thickness of 2 to 3 micrometers and a surface roughness Ra of less than 0.02 micrometers;
[0016] S32. Segmented pressurization and pressure holding molding: The press performs segmented pressing according to a preset program. In the first stage, it descends at a speed of 20 mm / s until it contacts the powder. In the second stage, it pressurizes at a speed of 5 mm / s to 10 MPa and holds for 1.0 second to expel air from the gaps between the powder. In the third stage, it continues to pressurize at a speed of 2 mm / s to the final molding pressure of 20-40 MPa and holds at the peak pressure for 3.0 to 5.0 seconds.
[0017] S33. Automatic Demolding and Conveying: After the pressure holding period, the lower mold ejector pin smoothly ejects the pressed spherical blank at a speed of 15 mm / s. The blank is then picked up by a vacuum suction cup on a six-axis robot arm and placed on a V-groove synchronous conveyor belt for transport to the next station. The entire process is fully automated with a cycle time of less than 20 seconds. The blank at this stage is called a preformed blank, with a diameter of 1.15 to 1.25 times that of the target sintered sphere and a relative density of 55% to 58% of the theoretical density.
[0018] Automated bagging, vacuuming, and heat sealing processes include the following steps:
[0019] S41. Automatic positioning and bagging of preform: The V-groove synchronous conveyor belt transports the preform to the integrated bagging and vacuum sealing workstation; the machine vision system performs three-dimensional positioning of the preform, guiding another robotic arm to put a pre-made polyurethane elastomer bag over the preform. The polyurethane elastomer bag has a thickness of 0.8 mm to 1.2 mm, and its inner diameter is in an interference fit with the outer diameter of the preform of 0.5% to 1.0%.
[0020] S42. Deep vacuuming: After bagging is completed, the bag opening is clamped by a vacuum sealing head. This sealing head is connected to a two-stage vacuum system consisting of a molecular pump and a mechanical pump to evacuate the bag until the vacuum level is better than 1.0 x 10^-2 Pa, and maintain this vacuum level for no less than 15 seconds to completely remove the air remaining on the surface of the blank and in the opening pores.
[0021] S43. High-frequency induction heat sealing: While maintaining vacuum, the bag opening is rapidly heated by a high-frequency induction heating device to reach a melting temperature of 180 degrees Celsius within 1.5 seconds. Then, a pressure of 0.5 MPa is applied to press and seal the bag. After cooling for 0.5 seconds, a completely airtight seal with a width of not less than 5 mm is formed. The sealed component is called the blank to be pressed package.
[0022] Ultra-high pressure cold isostatic pressing technology includes the following steps:
[0023] S51. Automatic loading: The blanks to be pressed are loaded in batches into the autoclave basket of the cold isostatic press through an automated track conveying system;
[0024] S52. Liquid medium pressurization: Seal the high-pressure vessel and pump water into the vessel as the pressure transmission medium; start the booster pump and steadily increase the pressure at a rate of 20 MPa to 30 MPa per minute until the final set pressure of 150-250 MPa is reached.
[0025] S53. Pressure Holding and Depressurization: After the pressure inside the autoclave reaches the set value, maintain the peak pressure for 180 to 240 seconds, so that the pressure is evenly transmitted to all parts of the billet through the elastomer bag, achieving secondary densification of the billet; after the pressure holding is completed, depressurize at a rate of 30 to 40 MPa per minute until the pressure drops to atmospheric pressure.
[0026] S54. Automatic unloading and unpacking: The autoclave is opened and the basket is automatically lifted out. The robot removes the package of the billet after cold isostatic pressing and uses a special cutting device to cut the elastomer bag along the sealing line to remove the billet. The billet at this time is called a high-density green billet, and its relative density reaches 65% to 68% of the theoretical density.
[0027] High-temperature sintering includes the following steps:
[0028] S61. Loading of high-temperature sintering furnace: High-density green billets are loaded into high-temperature saggers, stacked on kiln cars, and pushed into the tunnel kiln.
[0029] S62. Programmed temperature sintering: Perform temperature sintering according to the following program: raise the temperature from room temperature to 1200 degrees Celsius at a rate of 5.0 degrees Celsius per minute; then raise the temperature from 1200 degrees Celsius to the final sintering temperature of 1400-1500 degrees Celsius at a rate of 3.0 degrees Celsius per minute.
[0030] S63. Heating and Cooling: Hold at a final sintering temperature of 1500 degrees Celsius for 360 to 720 minutes to ensure sufficient grain growth and densification. After holding, turn off the heating power and allow the furnace to cool naturally to below 100 degrees Celsius in the environment before opening the furnace and taking out the finished product.
[0031] Comprehensive performance testing includes the following steps:
[0032] S71. Physical property testing: The sintered alumina ceramic spheres shall be tested, and their final diameter shall be 20 mm to 100 mm, sphericity tolerance shall be less than 1 mm, bulk density shall be greater than or equal to 3.7-3.9 g / cm³, and apparent porosity shall be less than 0.1%.
[0033] S72. Mechanical property testing: The compressive strength is tested using a crushing strength tester, and the average compressive strength of a single ball is required to be greater than 250 MPa; the surface hardness is measured using a Rockwell hardness tester, and the HRA hardness is required to be greater than or equal to 92.0; the wear resistance is tested using an abrasion tester, and the wear rate is required to be less than or equal to 0.01 mg / hour.
[0034] S73. Microstructure analysis: The microstructure after polishing and etching is observed by scanning electron microscopy (SEM). The grain size should be uniform, with the average grain size controlled between 0.4 micrometers and 0.8 micrometers. There should be no abnormally large grains, clear grain boundaries, and no obvious glass phase or microcracks.
[0035] The beneficial effects of this invention are as follows:
[0036] 1. The present invention discloses a method for preparing large-sized alumina ceramic balls with high wear resistance and high strength. By performing ultrafine and homogenization composite treatment on the main raw materials, the uniformity and stability of the slurry are improved, laying the foundation for subsequent molding.
[0037] 2. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to the present invention uses spray granulation technology to generate powder with good physical properties, which can significantly improve the forming quality of the green body.
[0038] 3. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength described in this invention uses a servo electric press to complete the initial automatic machine pressing preforming, combined with bagging, vacuuming and heat sealing treatment, which effectively reduces surface defects of the blank.
[0039] 4. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength described in this invention achieves secondary densification of the green body by utilizing ultra-high pressure cold isostatic pressing technology, which significantly improves the relative density of the green body.
[0040] 5. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength described in this invention avoids cracking of the green body and ensures the integrity of the degreasing process by controlling the degreasing process through a multi-stage procedure.
[0041] 6. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to the present invention ensures uniform grain growth and densification by sintering in a high-temperature environment, thereby obtaining excellent physical, mechanical and microstructural properties. Attached Figure Description
[0042] The invention will now be further described with reference to the accompanying drawings.
[0043] Figure 1 This is a schematic diagram of the process flow for preparing high-wear-resistant, high-strength, large-size alumina ceramic balls in an embodiment of the present invention. Detailed Implementation
[0044] This invention provides a method for preparing large-sized alumina ceramic balls with high wear resistance and high strength, the process flow of which is as follows: Figure 1As shown, the invention includes an intermittent ball mill, a spray granulation tower, a servo press, a bagging and vacuum sealing workstation, a cold isostatic press, a high-temperature sintering furnace, and comprehensive performance testing equipment. The technical solution of this invention is described in detail below with reference to the accompanying drawings and specific implementation steps.
[0045] In the main raw material processing stage, the raw materials are first prepared through precise weighing and feeding. Alumina micro powder with an α-phase purity of 90% to 99.99% is selected as the main raw material, with its D50 median particle size controlled within the range of 0.35 μm to 0.45 μm and specific surface area controlled between 12.5 m² / g and 14.5 m² / g. Polyvinyl alcohol (PVA) with a molecular weight of 1750±50 and a degree of hydrolysis of 98.5±0.5% is selected as the binder, added at 1.8% to 2.2% of the dry weight of the main raw material; ammonium polyacrylate is selected as the dispersant, added at 0.45% to 0.55% of the dry weight of the main raw material; polyethylene glycol (PEG-400) is selected as the plasticizer, added at 0.9% to 1.1% of the dry weight of the main raw material; and oleic acid is selected as the lubricant, added at 0.5% to 0.6% of the dry weight of the main raw material. All the above components, along with deionized water, are added to the grinding jar of an intermittent ball mill. The resistivity of the deionized water is not less than 18 megohm-cm. The grinding jar is lined with high-alumina material, and the grinding media consists of high-alumina balls with a diameter of 3 mm to 10 mm. The ball-to-material mass ratio is controlled at 3.5:1 to 4.5:1. The grinding jar is mounted on the intermittent ball mill and driven to rotate via a transmission mechanism at a speed set to 20 to 30 rpm. A circulating water jacket cooling system is connected to the outer wall of the grinding jar to maintain the jar temperature below 40 degrees Celsius. After continuous wet grinding for 28 to 32 hours, the slurry is tested using an online laser particle size analyzer to ensure that the D90 particle size is not greater than 0.95 micrometers. Subsequently, the slurry is passed through a high-gradient electromagnetic separator with a magnetic flux density of 1.2 Tesla to remove magnetic impurities, and then transferred to a stainless steel aging tank for sealed aging. The aging tank is set at a negative pressure of 0.01 MPa and a temperature of 25±3 degrees Celsius and maintained for 48 to 60 hours to promote the uniform adsorption and hydrolysis of organic additives.
[0046] After aging, the slurry is pumped to the atomizer in the spray granulation tower via a peristaltic pump. The flow rate of the peristaltic pump is precisely controlled between 25.0 liters / hour and 30.0 liters / hour. The atomizer is a high-speed centrifugal type with a disc diameter of 120 mm and a rotation speed set between 18,000 rpm and 22,000 rpm. The inlet hot air temperature of spray drying tower 2 is set between 175°C and 185°C, and the outlet temperature is between 90°C and 100°C. A slight negative pressure is maintained inside the tower. The dried powder is collected in two stages through the discharge valve at the bottom of the main tower and a cyclone separator, with a collection efficiency greater than 99.5%. The collected granulated powder was subjected to performance testing. The required moisture content was controlled between 0.40% and 0.60%, the loose density between 0.90 g / cm³ and 1.05 g / cm³, the tapped density between 1.15 g / cm³ and 1.30 g / cm³, and the flowability was measured using a Hall effect flow meter, requiring a flow rate of less than or equal to 25.0 s / 50 g. The powder was sieved using 200-mesh and 300-mesh standard sieves, and only the powder that passed through the 200-mesh sieve but was retained on the 300-mesh sieve was used for subsequent pressing and molding.
[0047] A servo press is used for the initial preforming of the blank. It features a closed-loop control system with a pressure control accuracy of ±0.1%FS and a position control accuracy of ±0.005 mm. An integrated weighing feeding system precisely fills the mold cavity with screened, qualified powder, with the mass error of each feeding controlled within ±0.05%. The mold is made of cemented carbide, with its inner surface treated with a diamond-like carbon coating. The coating thickness is 2 to 3 micrometers, and the surface roughness Ra is less than 0.02 micrometers. The press executes segmented pressing according to a preset program. The first stage involves descending at 20 mm / s until contact with the powder. The second stage involves increasing the pressure to 10 MPa at 5 mm / s and holding for 1.0 second to expel air from the powder gaps. The third stage involves continuing to increase the pressure at 2 mm / s to the final forming pressure of 20-40 MPa and holding at the peak pressure for 3.0 to 5.0 seconds. After the pressure holding period, the lower die ejector smoothly ejects the pressed spherical blank at a speed of 15 mm / s. The blank is then grasped by a vacuum suction cup on a six-axis robotic arm and placed on a V-groove synchronous conveyor belt for transport to the next station. The entire process is fully automated, with a cycle time of less than 20 seconds. The blank at this stage is called a preform, with a diameter 1.15 to 1.25 times that of the target sintered sphere and a relative density reaching 55% to 58% of the theoretical density.
[0048] The preform is conveyed to the bagging and vacuum sealing workstation via a V-groove synchronous conveyor belt. A machine vision system performs 3D positioning of the preform, guiding a robotic arm to place a pre-fabricated polyurethane elastomer bag over the preform. The bag thickness is 0.8 mm to 1.2 mm, and its inner diameter has an interference fit with the outer diameter of the preform at 0.5% to 1.0%. After bagging, the bag opening is clamped by a vacuum sealing head connected to a two-stage vacuum system consisting of a molecular pump and a mechanical pump. The bag is evacuated until a vacuum level better than 1.0 x 10⁻² Pa is achieved, and this vacuum level is maintained for at least 15 seconds. While maintaining the vacuum, the bag opening is rapidly heated using a high-frequency induction heating device, reaching a melting temperature of 180 degrees Celsius within 1.5 seconds. A pressure of 0.5 MPa is then applied for compression sealing. After cooling for 0.5 seconds, a completely airtight seal with a width of at least 5 mm is formed. The sealed component is called the preform bag.
[0049] The billet casings are loaded in batches into the autoclave basket of the cold isostatic press via an automated track conveyor system. After the autoclave is sealed, water is pumped into the autoclave as the pressure transmission medium. The booster pump is started, and the pressure is steadily increased at a rate of 20 to 30 MPa per minute until the final set pressure of 150-250 MPa is reached. After the pressure inside the autoclave reaches the set value, this peak pressure is maintained for 180 to 240 seconds, allowing the pressure to be evenly transmitted to all parts of the billet through the elastomer bag, achieving secondary densification of the billet. After the pressure holding is completed, the pressure is controlled to be released at a rate of 30 to 40 MPa per minute until the pressure drops to atmospheric pressure. After the autoclave is opened, the basket is automatically lifted out, and a robot removes the billet casings after cold isostatic pressing. A special cutting device is used to cut the elastomer bag along the sealing line and remove the billet. At this point, the billet is called a high-density green billet, with a relative density of 65% to 68% of the theoretical density.
[0050] High-density green billets are placed in high-temperature saggers and stacked on kiln cars, then pushed into a tunnel kiln for programmed temperature-controlled sintering. The temperature is increased according to the following procedure: from room temperature to 1200 degrees Celsius at a rate of 5.0 degrees Celsius per minute, then from 1200 degrees Celsius to the final sintering temperature of 1400-1500 degrees Celsius at a rate of 3.0 degrees Celsius per minute. The final sintering temperature of 1500 degrees Celsius is held for 360 to 720 minutes to ensure sufficient grain growth and densification. After the holding period, the heating power is turned off, and the furnace is allowed to cool naturally to below 100 degrees Celsius before the finished product is removed from the furnace.
[0051] The finished product undergoes physical, mechanical, and microstructure analysis using comprehensive performance testing equipment. Physical performance testing requires a finished product diameter of 20 mm to 100 mm, a sphericity tolerance of less than 1 mm, a bulk density of ≥3.7-3.9 g / cm³, and an apparent porosity of less than 0.1%. Mechanical performance testing employs a crushing strength tester to measure compressive strength, requiring an average compressive strength per sphere greater than 250 MPa; a Rockwell hardness tester to measure surface hardness, requiring an HRA hardness greater than or equal to 92.0; and an abrasion tester to test wear resistance, requiring an wear rate less than or equal to 0.01 mg / h. Microstructure analysis involves observing the microstructure after polishing and etching using a scanning electron microscope, requiring uniform grain size, an average grain size controlled between 0.4 μm and 0.8 μm, no abnormally large grains, clear grain boundaries, and no obvious glass phase or microcracks. To better enable those skilled in the art to fully understand and implement this invention, the specific implementation principle of the invention is further explained below in conjunction with a specific application scenario.
[0052] In the main raw material processing stage, alumina micro powder and other auxiliary materials are first refined and homogenized using an intermittent ball mill. High-purity α-phase alumina micro powder is selected as the main raw material, and its particle size distribution and specific surface area are strictly controlled to ensure the density and uniformity of the green body during subsequent molding and sintering. The amounts of binder, dispersant, plasticizer, and lubricant added are precisely calculated to ensure the fluidity of the slurry while avoiding excessive organic content that could lead to porosity or cracks during sintering. During ball milling, a circulating water jacket cooling system maintains the tank temperature below 40 degrees Celsius to prevent chemical changes or particle agglomeration due to overheating. An online laser particle size analyzer monitors the particle size distribution of the slurry in real time, ensuring that the D90 particle size is no greater than 0.95 micrometers, thus providing a high-quality base slurry for subsequent spray granulation. A high-gradient electromagnetic separator with a magnetic flux density of 1.2 Tesla effectively removes magnetic impurities that may have been introduced during grinding, further improving the purity of the slurry. The negative pressure environment and constant temperature conditions in the stainless steel aging tank promote the adsorption and hydrolysis of organic additives, thereby enhancing the stability of the slurry.
[0053] In the spray granulation stage, a high-speed centrifugal atomizer transforms the aged slurry into powder with specific physical properties. A peristaltic pump delivers the slurry to the atomizer with precise flow control, ensuring the formation of uniform droplets during atomization. The inlet hot air temperature of the spray drying tower is set at 175°C to 185°C, and the outlet temperature at 90°C to 100°C. This temperature range allows for rapid evaporation of moisture while preventing powder agglomeration or decomposition due to overheating. The dried powder is efficiently collected by a cyclone separator with a collection efficiency greater than 99.5%, minimizing powder loss. After sieving, only powder passing through 200 mesh and retained within 300 mesh is retained. This particle size range provides excellent flowability and molding properties, making it an ideal raw material for subsequent preforming by a servo press.
[0054] During the initial preforming of the blank using a servo press, a closed-loop control system achieves high-precision control of pressure and position. A weighing-type feeding system precisely fills the mold cavity with screened, qualified powder, with the quality error of each feeding controlled within ±0.05%, ensuring the consistency of the blank. The inner surface of the mold is treated with a diamond-like carbon coating, reducing friction between the powder and the mold and minimizing surface damage during demolding. In the segmented pressing process, the first stage involves a faster downward movement to contact the powder; the second stage uses lower speed to pressurize and expel air from the powder gaps; and the third stage reaches the final forming pressure at a slower speed and maintains the peak pressure for a certain period to ensure the uniformity of the internal structure of the blank. A vacuum suction cup on a six-axis robotic arm smoothly grips the preformed blank and places it on a V-groove synchronous conveyor belt, achieving full automation throughout the process and significantly improving production efficiency.
[0055] In the bagging and vacuum sealing workstation, a machine vision system performs three-dimensional positioning of the preform, ensuring that the polyurethane elastomer bag is accurately fitted onto the outside of the preform. The interference fit design between the bag thickness and the preform's outer diameter allows the bag to tightly adhere to the preform surface, reducing the possibility of displacement during cold isostatic pressing. A secondary vacuum system performs deep vacuuming inside the bag until the vacuum level is better than 1.0 x 10^-2 Pa, maintaining this vacuum level for at least 15 seconds to completely remove residual air from the preform surface and openings, thus preventing cracking of the preform due to gas expansion during cold isostatic pressing. A high-frequency induction heating device rapidly heats the bag opening and seals it in a short time, ensuring the bag's airtightness and providing a reliable guarantee for subsequent cold isostatic pressing.
[0056] The cold isostatic press transmits pressure through a liquid medium to achieve secondary densification of the billet. The optimized pressure increase rate and holding time within the autoclave ensure that pressure is evenly distributed throughout the billet via an elastomer bag, preventing localized stress concentration that could lead to cracking or deformation. After the holding period, pressure is released at a controlled rate, reducing internal stress caused by sudden pressure drops. The relative density of the billet after cold isostatic pressing reaches 65% to 68% of the theoretical density, laying a solid foundation for subsequent high-temperature sintering.
[0057] The programmed heating sintering process in the tunnel kiln is divided into multiple stages. The temperature is increased from room temperature to 1200 degrees Celsius at a rate of 5.0 degrees Celsius per minute, and then further increased to the final sintering temperature of 1400-1500 degrees Celsius at a rate of 3.0 degrees Celsius per minute. This segmented heating method effectively avoids thermal stress cracking of the green body due to excessively rapid heating. The final sintering temperature of 1500 degrees Celsius is held for 360 to 720 minutes to ensure sufficient grain growth and densification. The finished product is then removed from the kiln after natural cooling to below 100 degrees Celsius, thus avoiding thermal stress cracking caused by rapid cooling.
[0058] Comprehensive performance testing equipment performs a full analysis of the finished product, including its physical properties, mechanical properties, and microstructural characteristics. By testing the diameter, sphericity tolerance, bulk density, and apparent porosity of the finished product, its compliance with design requirements is verified. A crushing strength tester and a Rockwell hardness tester are used to test the compressive strength and surface hardness of the finished product, respectively, while an abrasion tester evaluates its wear resistance. A scanning electron microscope is used to observe the microstructure of the finished product, ensuring uniform grain size without abnormal growth, clear grain boundaries without obvious glassy phases or microcracks. These test results not only verify the performance indicators of the finished product but also provide important references for optimizing process parameters.
[0059] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing large-size alumina ceramic balls with high wear resistance and high strength, characterized in that: Includes the following steps: S1: The main raw materials are subjected to a combination of ultrafine and homogenization treatment to generate a slurry suitable for subsequent processing; S2: Spray granulation technology is used to transform slurry into powder with specific physical properties; S3: The initial automatic machine pressing preforming is completed by a servo electric press to form a preformed blank; S4: Automated bagging, vacuuming and heat sealing of preformed blanks to reduce surface defects; S5: Secondary densification is achieved by using ultra-high pressure cold isostatic pressing technology to increase the relative density of the billet; S6: Sintering is carried out at high temperature to ensure uniform grain growth and densification; S7: Conduct comprehensive performance testing on the finished product to verify its physical, mechanical, and microstructural properties.
2. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to claim 1, characterized in that: The process of ultra-fine and homogenized compound treatment of the main raw material in S1 includes: S11: Precise Weighing and Feeding of Raw Materials: Alumina micro-powder with an α-phase purity of 90% to 99.99% is selected as the main raw material, with its D50 median particle size controlled within the range of 0.35 micrometers to 0.45 micrometers and its specific surface area controlled between 12.5 m² / g and 14.5 m² / g; a binder with a molecular weight of 1750±50 and a degree of hydrolysis of 98.5±0.5% is selected, with its addition amount being 1.8% to 2.2% of the dry weight of the main raw material; a dispersant is selected, with its addition amount being 0.45% to 0.55% of the dry weight of the main raw material; a plasticizer is selected. The amount of the additive is 0.9% to 1.1% of the dry weight of the main raw material; oleic acid is selected as the lubricant, and its amount of additive is 0.5% to 0.6% of the dry weight of the main raw material; the above-mentioned components, weighed to an accuracy of one ten-thousandth, are added together with deionized water into a ball mill jar, wherein the resistivity of the deionized water is not less than 18 megohms·cm, the ball mill jar is a high-alumina lined intermittent ball mill, the high-alumina lining has a purity of 92 or 95, the ball milling media is high-alumina, with a purity of 92 or 95, its diameter is 3 mm to 10 mm, and the ball-to-material mass ratio is controlled at 3.5:1 to 4.5:1; S12: Intermittent ball milling: Start the intermittent ball mill, set the rotation speed to 20 to 30 rpm, and continuously wet mill for 28 to 32 hours in an environment with a temperature control of 22±2 degrees Celsius. During this period, the outer wall temperature of the tank is maintained at no more than 40 degrees Celsius through a circulating water jacket cooling system. After the ball milling is completed, the slurry is tested by an online laser particle size analyzer to ensure that the D90 particle size of the slurry is no greater than 0.95 micrometers. S13: Iron removal and aging of slurry: The ball-milled slurry is passed through a high-gradient electromagnetic iron remover with a magnetic flux density of 1.2 Tesla to remove magnetic impurities that may have been mixed in during the grinding process; the iron-removed slurry is transferred to a stainless steel aging tank with a slow stirring device and sealed and aged for 48 to 60 hours under a negative pressure of 0.01 MPa and a temperature of 25±3 degrees Celsius to promote the uniform adsorption and hydrolysis of organic additives.
3. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to claim 1, characterized in that: In step S2, spray granulation technology is used to transform the slurry into powder with specific physical properties, including: S21: Slurry delivery and atomization: The aged slurry is delivered to the atomizer of the centrifugal spray granulation tower via a peristaltic pump. The flow rate of the peristaltic pump is precisely controlled between 25.0 liters / hour and 30.0 liters / hour. The atomizer is a high-speed centrifugal type with a disc diameter of 120 mm and a rotation speed set between 18,000 rpm and 22,000 rpm. S22: Drying and Collection: The inlet hot air temperature of the spray drying tower is set to 175°C to 185°C, and the outlet temperature is set to 90°C to 100°C. A slight negative pressure is maintained inside the tower. The dried powder is collected in two stages through the discharge valve at the bottom of the main tower and a cyclone separator, ensuring a collection efficiency of greater than 99.5%. S23: Powder performance characterization and screening: The collected granulated powder is subjected to performance testing. The required moisture content is controlled between 0.40% and 0.60%, the loose density is between 0.90 g / cm³ and 1.05 g / cm³, the tapped density is between 1.15 g / cm³ and 1.30 g / cm³, and the flowability is measured by a Hall effect flow meter, requiring a flow rate of less than or equal to 25.0 s / 50 g. The powder is screened using 200 mesh and 300 mesh standard sieves. Only the powder that passes through the 200 mesh sieve and is retained in the 300 mesh sieve is used for subsequent pressing and molding.
4. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to claim 1, characterized in that: in step S3, the initial automatic machine pressing pre-forming is completed by a servo electric press, including: S31: Precise feeding by servo electric press: A servo electric press with a closed-loop control system is used, with a pressure control accuracy of ±0.1%FS and a position control accuracy of ±0.005 mm; through an integrated weighing feeding system linked to the press control system, the qualified powder screened in S3 is precisely filled into the mold cavity, and the mass error of each feeding is controlled within ±0.05%; the mold is made of cemented carbide, and its inner surface is treated with diamond-like carbon coating with a coating thickness of 2 to 3 micrometers and a surface roughness Ra of less than 0.02 micrometers; S32: Segmented pressurization and pressure holding molding: The press performs segmented pressing according to a preset program. In the first stage, it descends at a speed of 20 mm / s until it contacts the powder. In the second stage, it pressurizes at a speed of 5 mm / s to 10 MPa and holds for 1.0 second to expel air from the gaps between the powder. In the third stage, it continues to pressurize at a speed of 2 mm / s to the final molding pressure of 20-40 MPa and holds at the peak pressure for 3.0 to 5.0 seconds. S33: Automatic Demolding and Conveying: After the pressure holding period, the lower mold ejector pin smoothly ejects the pressed spherical blank at a speed of 15 mm / s. The blank is then picked up by a vacuum suction cup on a six-axis robot arm and placed on a V-groove synchronous conveyor belt for transport to the next station. The entire process is fully automated with a cycle time of less than 20 seconds. The blank at this stage is called a preformed blank, with a diameter of 1.15 to 1.25 times that of the target sintered sphere and a relative density of 55% to 58% of the theoretical density.
5. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to claim 1, characterized in that: The S4 process involves automated bagging, vacuuming, and heat sealing of the preform, including: S41: Automatic positioning and bagging of preform: The V-groove synchronous conveyor belt transports the preform to the integrated bagging and vacuum sealing workstation; the machine vision system performs three-dimensional positioning of the preform, guiding another robotic arm to put a pre-made polyurethane elastomer bag over the preform. The polyurethane elastomer bag has a thickness of 0.8 mm to 1.2 mm, and its inner diameter is in an interference fit with the outer diameter of the preform of 0.5% to 1.0%. S42: Deep vacuuming: After bagging is completed, the bag opening is clamped by a vacuum sealing head, which is connected to a two-stage vacuum system consisting of a molecular pump and a mechanical pump to evacuate the bag until the vacuum level is better than 1.0×10⁻² Pa, and maintain this vacuum level for no less than 15 seconds to completely remove the air remaining on the surface of the blank and in the opening pores. S43: High-frequency induction heat sealing: While maintaining vacuum, the bag opening is rapidly heated by a high-frequency induction heating device to reach a melting temperature of 180 degrees Celsius within 1.5 seconds. Then, a pressure of 0.5 MPa is applied to press and seal the bag. After cooling for 0.5 seconds, a completely airtight seal with a width of not less than 5 mm is formed. The sealed component is called the blank to be pressed package.
6. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to claim 1, characterized in that: The S5 process utilizes ultra-high pressure cold isostatic pressing technology to achieve secondary densification, including: S51: Automatic loading: The blanks to be pressed are loaded in batches into the autoclave basket of the cold isostatic press via an automated track conveying system; S52: Liquid medium pressurization: Seal the high-pressure vessel and pump water into the vessel as the pressure transmission medium; start the booster pump and steadily increase the pressure at a rate of 20 MPa to 30 MPa per minute until the final set pressure of 150-250 MPa is reached. S53: Pressure holding and depressurization: After the pressure inside the autoclave reaches the set value, maintain the peak pressure for 180 to 240 seconds, so that the pressure is evenly transmitted to all parts of the billet through the elastomer bag, and the billet is densified twice; after the pressure holding is completed, depressurize at a rate of 30 to 40 MPa per minute until the pressure drops to atmospheric pressure. S54: Automatic unloading and unpacking: The autoclave is opened, the basket is automatically lifted out, and the robot removes the package of the billet after cold isostatic pressing. A special cutting device is used to cut the elastomer bag along the sealing line and remove the billet. The billet at this time is called a high-density green billet, and its relative density reaches 65% to 68% of the theoretical density.
7. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to claim 1, characterized in that: The sintering process in S6 at a high temperature includes: S61: Loading of high-temperature sintering furnace: High-density green billets are loaded into high-temperature saggers, stacked on kiln cars, and pushed into the tunnel kiln. S62: Programmed temperature sintering: Perform temperature sintering according to the following program: increase the temperature from room temperature to 1200 degrees Celsius at a rate of 5.0 degrees Celsius per minute; then increase the temperature from 1200 degrees Celsius to the final sintering temperature of 1400-1500 degrees Celsius at a rate of 3.0 degrees Celsius per minute. S63: Heating and cooling: Hold at a final sintering temperature of 1500 degrees Celsius for 360 to 720 minutes to ensure sufficient grain growth and densification; after the heating is completed, turn off the heating power and allow the furnace to cool naturally to below 100 degrees Celsius in the environment before opening the furnace and taking out the finished product.
8. The method for preparing large-size alumina ceramic balls with high wear resistance and high strength according to claim 1, characterized in that: The S7 step involves comprehensive performance testing of the finished product, including: S71: Physical property testing: The sintered alumina ceramic spheres are tested, requiring a final diameter of 20 mm to 100 mm, a sphericity tolerance of less than 1 mm, a bulk density of ≥3.7-3.9 g / cm³, and an apparent porosity of less than 0.1%. S72: Mechanical property testing: The compressive strength is tested using a crushing strength tester, and the average compressive strength of a single ball is required to be greater than 250 MPa; the surface hardness is measured using a Rockwell hardness tester, and the hardness is required to be greater than or equal to 92.0; the wear resistance is tested using an abrasion tester, and the wear rate is required to be less than or equal to 0.01 mg / hour. S73: Microstructure analysis: The microstructure after polishing and etching is observed by scanning electron microscopy. The grain size is required to be uniform, with the average grain size controlled between 0.4 micrometers and 0.8 micrometers. There should be no abnormally large grains, clear grain boundaries, and no obvious glass phase or microcracks.
Citation Information
Patent Citations
Preparation method of high-strength electric smelting zirconia ceramic ball
CN103232238B
A dense, high-hardness, and high-strength silicon nitride ceramic sphere, its preparation method, and its application.
CN113461426B
Carburization method for hard alloy in vacuum sintering furnace
CN104493161A
99 alumina ceramic cylinder sleeve inner liner material used for petroleum drilling well and preparation method thereof
CN104496423A
Manufacturing method of high-density pure-rhenium test tube
CN106270530A